Quality of life, coping strategeis and their associated factors among Hospital house officers in Kelantan - A/L Narayansamy, Ramesh (2020)
Introduction: Over the years, medicine has proven itself to be an occupational field that quite severely affects the quality of life (QOL) of its employees. In Malaysia, Housemanship is a period of structured supervised practical training upon completion of medical school. It has been said to be the most challenging period of one's medical career. Coping has always been associated with QOL as a feature of adaptation. Objective: This study was aimed to determine the QOL, coping strategies and their associated factors among hospital house officers in Kelantan. Methodology: A cross-sectional study was conducted from April 2018 to April 2020 in all government hospitals of Kelantan which were Hospital Universiti Sains Malaysia (HUSM), Hospital Raja Perempuan Zainab II (HRPZ II), Hospital Tanah Merah (HTM) and Hospital Kuala Krai (HKK). A total of 370 house officers registered to the Malaysian Medical Council who have been working in public hospitals of Kelantan for at least eight months participated in this study. The validated Malay versions of World Health Organization Quality of Life-BREF (WHOQOL-BREF) and Brief Coping Orientation to Problems Experienced Scale (Brief COPE) questionnaires were self-administered. Results: For QOL, the scores for physical, psychological, social relationships and environmental health domains were 44%, 56.0%, 56.0% and 63.0% respectively. Majority of the house officers had perceived their QOL to be ‘moderate’ (57.8%) and ‘satisfied’ with their health (43.0%). Mean [standard deviation (SD)] of the five most frequently used coping strategies were religion [6.56 (1.10)], self-blame [6.51 (0.97)], positive reframing [6.33 (1.09)], the use of instrumental support [6.33 (1.20)] and planning [6.22 (1.17)]. Also, it was reported that problem focused coping (72.8%) and emotion focused coping (68.1%) were almost equally practised by our study participants Not being extended in service [Adjusted regression (b) [(95% confidence interval (CI)]: 3.09 (0.42, 5.76) p=0.023], using emotional support [Adjusted b (95% CI): 1.92 (0.88, 2.95) p<0.001] and planning [Adjusted b (95% CI): 1.10 (0.08, 2.12) p=0.034] were significantly associated with higher total scores of QOL. Female house officers [Adjusted b (95% CI): 0.27 (0.02, 0.52) p=0.005] and those attached to their final posting [Adjusted b (95% CI): 0.82 (0.12, 1.77) p=0.038] were predisposed to a higher total score of problem focused coping. Being male [Adjusted b (95% CI): 0.22 (-0.89, 1.34) p=0.046], Malay ethnicity [Adjusted b (95% CI): 0.23 (0.20, 0.52) p=0.013] and being posted to HRPZ II [Adjusted b (95% CI): 1.22 (0.34, 2.11) p=0.001], HTM [Adjusted b (95% CI): 1.56 (0.55, 2.58) p<0.001] as well as HKK [Adjusted b (95% CI): 1.69 (0.57, 2.82) p<0.001] were factors found to be associated to a higher total score of emotion focused coping strategies. Conclusion: Majority of the hospital house officers in Kelantan had generally perceived their QOL and health to be moderate and satisfactory. The choice of certain coping strategies strongly influences various aspects of their QOL. Among them, several emotion focused coping strategies were found to be most prevalent. Finally, certain socio-demographic and occupational factors were observed to be associated with the different types of coping strategies among them.